HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA GEOGRAFI SMAN 5 PADANG (JURNAL SPASIAL, 2016)
This study aims to gather information, analyze and discuss data on Learning Motivation Relationship with Learning Outcomes of Geography students of SMAN 5 Padang. Type correlational study population was all students of class XI IPS consists of four local numbering 162 people. Samples were taken by proportional random sampling technique, where each class is taken randomly with a proportion of 50% so that the sample was 81 students. These results indicate there is a relationship between motivation and learning outcomes geography class XI IPS SMA N 5 Padang, the strength of the relationship between motivation and learning outcomes geographies including medium and small contributions are included.